Cyclicality and fiscal policy in the Caribbean : is there a case for fiscal rules? - Samuel, Wendell ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2008)
Examines the fiscal performance of selected Caribbean countries by looking at the structural balance and discusses the applicability of fiscal rules.